As Transformações da Indústria Musical na Era das Plataformas Digitais: Uma Análise em Termos de Economias de Rede - Cavatti, Gabriel dos Santos (2020)
Digital platforms have transformed the music industry in these last two decades. Due to new technologies, like storage, streaming and music sales, the recording industry was changed dramatically during this period. Its revenue dwindled in about 40% in 15